2015
DOI: 10.1002/bdm.1876
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Psychological Factors Associated with Social Discounting

Abstract: The social discounting paradigm is a powerful means of quantifying altruism in humans, who are typically willing to forgo some amount of personal earnings in exchange for increased earnings for another person. The amount of money that people are willing to forgo decreases with increasing social distance. In this study, we examined variables related to sex, intolerance of uncertainty, and empathy, all of which are theorized to affect the social discounting rate. Participants (27 men and 28 women) completed meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…We expected that cognitive load flattened the social discount function, reflecting the hypothesized social-distance-dependent cognitive-load effects on generosity. Finally, since one recent study identified different psychological predictors of social discounting in men and women [25], we also suggest a potential gender difference in cognitive load effects on social discounting.…”
Section: Introductionmentioning
confidence: 50%
“…We expected that cognitive load flattened the social discount function, reflecting the hypothesized social-distance-dependent cognitive-load effects on generosity. Finally, since one recent study identified different psychological predictors of social discounting in men and women [25], we also suggest a potential gender difference in cognitive load effects on social discounting.…”
Section: Introductionmentioning
confidence: 50%
“…Participants in Boyer et al's (2012) experiment included Chinese employees and Kenyan herders, while Sharp et al (2012) in turn studied 2 nd to 12 th grade boys. Yi et al (2011) employed active methamphetamine users as subjects, and Olson et al (2016) 18-45 year old community members.…”
Section: Subjectsmentioning
confidence: 99%
“…Other studies, notably those investigating the psychology of social discounting, collect data using psychometric instruments. One example is Olson et al (2016), who employs the Intolerance of Uncertainty Scale (IUS), the Empathy Quotient (EQ60), and the WASI intelligence test, while Böckler et al (2016) utilise the Prosocialness Scale, Machiavelli Index, and Interpersonal Reactivity Index (IRI).…”
Section: Settingsmentioning
confidence: 99%
See 2 more Smart Citations